An Assessment of Biochemical biomarkers alterations in COVID-19 patients: Biochemical Biomarkers Alterations in COVID-19 Patients - Javaid, Shehla; Maham, Miss; Abbas, Khizar; Rehman, Hafiz Muhammad; Kousar, Sumaira; Bashir, Fareeha; Gul, Sidra; jamil, Rahat (Pakistan BioMedical Journal, 2022)
COVID-19 (coronavirus disorder 2019) is a sickness as a result of a virulent virus named SARS-CoV-2 and turned into discovered in December 2019 in Wuhan, China. Objectives: To evaluate the most common biochemical parameters those are increased in COVID-19 positive patients and ultimately can be used as a diagnostic marker for the evaluation and staging of disease. Methods: This study included 200 COVID-positive patients confirmed with PCR. The clinical profile was recorded from various conventional laboratories. Data was analyzed statistically by applying sample t test to the data. Results: Total 200 patients were included in the study. Increased levels of various biochemical parameters have been found including ferritin, CRP and d- dimmer. D-dimer was elevated in 99.5 percent (n = 199) whereas 0.5 percent (n = 1) were normal and ferritin was elevated in 65.5 percent (n = 131) and was normal in 32.5 percent (n = 65). CRP was elevated in 81.5% (n=163) patients. Variations was also seen in Electrolytes like potassium was elevated in 53 % (n=106) and was low value in 8% (n= 16) while it remained normal in normal in 39% (n= 78). Sodium ions were high in 25.5% (n=51), reduced in 37.5% (n = 75) while 375 (n=74) were normal. Chloride was elevated in 32.5% reduced in 26% while it was normal in 41.5%. The metrics that remained normal were: urea (96.5%), creatinine (66.5%), total bilirubin (84%), platelets (86.5%), and TLC (73%). Ferritin, CRP and d-dimmer had a p value lower than 0.05 showing significant results. Conclusion: This study concluded that some parameters particularly d-dimer, ferritin, C reactive protein were considered to be predictive markers for the initial diagnose of COVID-19.